Optimisez la productivité de vos réunions (Assemble You, 2022)
Welcome to Assemble You Audio Learning. While teamwork and collaboration are essential elements in the business world and for professional development, however, surveys have revealed that meetings are the number one cause of wasted time at work. We'll look at how to reduce the number of meetings you host and how to schedule meetings that have truly actionable results. You will also learn how to better manage the preparation and follow-up process before and after meetings. Learning Objectives Learn how to run a productive meeting Learn what you need to do outside of the actual meeting to get the most out of your meeting time.